Knowledge, attitude and practice (KAP) towards visual impairment and visual rehabilitation among teachers in Malaysia - Mohd Taha, Nurul Maisarah; Musa, Azuwan (KAHS, IIUM, 2023)
Introduction: Visual impairment is one of the biggest public health concerns globally. It gives greater consequences to the children and their family members mainly on their education, employment, personal and social-emotional status. If the emphasis on the appropriate vision care and rehabilitation services are not rendered, the number of blind children is expected to rise significantly every year. Aim: This study aimed to assess the knowledge, attitude, and practice (KAP) towards visual impairment and visual rehabilitation among school teachers in Malaysia. Methodology: A total of 384 respondents were recruited in this study, and all the respondents completed the validated and reliable self-administered questionnaires on their KAP towards visual impairment and visual rehabilitation. Results: Most respondents (92.4%) have good KAP on visual impairment and visual rehabilitation despite only 4.2% of them had attended formal low vision course or training. There was a significant association between attending low vision training and high KAP among the teachers. Conclusion: The study gives an insight into the need for low vision course in the teacher’s curriculum in order to improve their learning experience and academic performance.